Multi-objective stochastic programming in fuzzy environments - Biswas, Animesh; De, Arnab Kumar (IGI Global, 2019)
"This book explores some emerging concepts on decision making models with simultaneous occurrence of fuzzy as well as stochastic uncertainties in a simple and systematic manner"--